2007
DOI: 10.1007/s12031-007-9019-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CAPON after Spinal Cord Injury in Rats

Abstract: The adaptor protein, carboxy-terminal PDZ ligand of nNOS (CAPON), regulates the distribution of neuronal nitric oxide synthase (nNOS) that increased after spinal cord injury (SCI) and produces the key signaling molecule nitric oxide (NO). But little is known about the role of CAPON in the pathological process of SCI. The main objective of the present study was to investigate expression of CAPON and nNOS in a spinal cord contusion model in adult rats. Real time-polymerase chain reaction (PCR) and Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…We next examined the involvement of neuroinflammation. Shao et al 20 reported that lipopolysaccharide (LPS) stimulation induces CAPON expression, and Cheng et al 21 proposed that CAPON increases after spinal cord injury. Therefore, neuroinflammation could also be involved in the elevation of CAPON expression under amyloid pathology.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the involvement of neuroinflammation. Shao et al 20 reported that lipopolysaccharide (LPS) stimulation induces CAPON expression, and Cheng et al 21 proposed that CAPON increases after spinal cord injury. Therefore, neuroinflammation could also be involved in the elevation of CAPON expression under amyloid pathology.…”
Section: Resultsmentioning
confidence: 99%
“…nNOS is expressed in many cell types in peripheral nervous system including Schwann cells of peripheral nerve (36), DRG neurons (37,38), and motoneurons, oligodendrocytes, and astrocytes of spinal cord (39,40). One can not exclude that it is also expressed in vasa nervorum considering recent report of the presence of nNOS in vascular endothelium (41).…”
Section: Discussionmentioning
confidence: 99%
“…16 After 1-time spinal cord injury or central nervous system infection, the expression of CAPON was increased, resulting from up-regulated expression of nNOS, thus maintaining the balance between nNOS and CAPON to prevent NO-induced neurotoxicity. 34,35 The present study showed that the expression of nNOS was increased and the expression of CAPON was decreased after ECS application once a day for 7 days, whereas the expression of nNOS was decreased and the expression of CAPON was increased after ECS application with propofol administration, implying the role of CAPON in regulating NO production by interfering with the activity of nNOS, PSD-95. Whether the expression of CAPON increased to regulate nNOS after 1-time ECS as the mechanism of compensation, or the level of CAPON would decrease after continuing ECS due to decompensation, is still a matter of debate; further investigation is necessary to confirm the fluctuation and its significance of CAPON at different time points after ECS.…”
Section: Discussionmentioning
confidence: 52%